Effective High-Order Iterative Methods via the Asymptotic Form of the Taylor-Lagrange Remainder - Isaac Fried (Journal of Applied Mathematics)
The asymptotic form of the Taylor-Lagrange remainder is used to derive some new, efficient, high-order methods to iteratively locate the root, simple or multiple, of a nonlinear function. Also derived are superquadratic methods that converge contrarily and superlinear and supercubic methods that converge alternatingly, enabling us not only to approach, but also to bracket the root.